In situ small‐angle X‐ray scattering investigation of X‐ray‐induced gold nanoparticle synthesis without stabilizer. Issue 6 (16th November 2021) - Li, Fangzuo; Xu, Qianqian; Xia, Wenjing; Zhang, Xiang; Zhao, Weidong; Zhou, Lili; Zhong, Haijian; Peng, Weijie; Liu, Zhiguo; Sun, Tianxi
Abstract : The X‐ray irradiation of gold salt aqueous solutions in the synthesis of gold nanoparticles (AuNPs) in the absence of any reducing agent and stabilizer has been followed by in situ small‐angle X‐ray scattering. The key parameters to obtain stable, monodispersed, bare AuNPs and the influence of the pH of the chemical solution on the final particles were studied. Abstract : The X‐ray irradiation of gold salt aqueous solutions in the synthesis of gold nanoparticles (AuNPs) in the absence of any reducing agent or stabilizer is presented. The size, dispersion, number of particles, yield and morphology evolution during the radiolytic formation of AuNPs were followed simultaneously using in situ small‐angle X‐ray scattering. This study provides an insight into the overall kinetics and formation mechanisms at the initial stage of AuNP synthesis without reductants and stabilizers. The pH‐dependent speciation of aqueous HAuCl4 and its influence on the synthesis, structure and properties of AuNPs were observed. The result sheds light on the key parameters required to obtain stable monomodal particles and the influence of the surface charge and reactivity of the chemical solution on the final particle size and shape.